Critical Reading and Literacy in EFL Context: A Systematic Literature Review - Aisyah, Shifak; Inawati, Iin; Pratolo, Bambang Widi (IKIP Siliwangi, 2025)
The purpose of this study is to summarize and critically analyze existing empirical research on critical reading and literacy in EFL classroom contexts. The descriptive statistics characterizing the studies (e.g., research designs, participant characteristics, settings) were presented alongside the qualitative content analysis findings results containing the emerging themes, which were arranged sequentially according to their prevalence. The research articles reviewed in this study met the following criteria: (1) peer-reviewed studies, (2) critical reading and literacy in EFL contexts, and (3) published within the last 9 years by using search engine databases (e.g., SINTA, Google Scholars) and reputable journal websites (e.g., journals.sagepub.com, tanfonline.com, link.springer.com). This analytical review revealed three emerging themes of findings informing the outcome of critical reading discourse enhancement in classroom context, critical thinking, and the challenges of integrating critical reading and literacy. The findings of this study should be able to shed light on what has been done thus far and highlight implications for future research and practice regarding critical reading and literacy.